Come to Texas : attracting immigrants, 1865-1915 - Rozek, Barbara J., 1945- (Centennial series of the Association of Former Students, Texas A & M University ;, 2003)
"Come to Texas" urged countless advertisements, newspaper articles, and private letters in the late nineteenth century. Expansive acres lay fallow, ready to be turned to agricultural uses. Entrepreneurial Texans knew that drawing immigrants to those lands meant greater prosperity for the state as a whole and for each little community in it. They turned their hands to directing the stream of spatial mobility in American society to Texas. They told the "Texas story" to whoever would read it. In this book, Barbara Rozek documents their efforts, shedding light on the importance of their words in peopling the Lone Star State and on the optimism and hopes of the people who sought to draw others.Rozek traces the efforts first of the state government (until 1876) and then of private organizations, agencies, businesses, and individuals to entice people to Texas. The appeals, in whatever form, were to hope?hope for lower infant mortality rates, business and farming opportunities, education, marriage?and they reflected the hopes of those writing. Rozek states clearly that the number of words cannot be proven to be linked directly to the number of immigrants (Texas experienced a population increase of 672 percent between 1860 and 1920), but she demonstrates that understanding the effort is itself important.Using printed materials and private communications held in numerous archives as well as pictures of promotional materials, she shows the energy and enthusiasm with which Texans promoted their native or adopted home as the perfect home for others.Texas is indeed an immigrant state?perhaps by destiny; certainly, Rozek demonstrates, by design.